2022
DOI: 10.3390/foods11030348
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and Wellness Profiles of Herbal Drinks Measured Using Different Questionnaire Designs

Abstract: The emotion and wellness profiles of herbal drinks were assessed using six different questionnaire designs. The questionnaire designs were constructed from two formats of questionnaire items, including words and sentences, and three types of measuring scales, including a rating scale (5-point intensity; 1 = ‘not at all’, 5 = ‘extremely’), a checklist scale (check-all-that-apply, CATA), and a combination of CATA and rating scales (rate-all-that-apply, RATA; 5-point intensity; 1 = ‘slightly’, 5 = ‘extremely’). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Part III – Expected sensory liking and emotional responses before receiving product information (Before) : Pictures of three products (P‐cp, P‐mp and P‐cp*mp) were presented to participants for them to virtually evaluate the expected overall sensory liking using a 9‐point hedonic scale, and the expected emotional responses elicited by each product using the check‐all‐that‐apply (CATA) method. The 35 emotional terms adopted from the EsSense Profile® (King & Meiselman, 2010) were translated into Thai by a group of English–Thai bilinguals and translated back to English by another group for meaning validation (Hanmontree et al ., 2022). In this part, participants did not receive additional product information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part III – Expected sensory liking and emotional responses before receiving product information (Before) : Pictures of three products (P‐cp, P‐mp and P‐cp*mp) were presented to participants for them to virtually evaluate the expected overall sensory liking using a 9‐point hedonic scale, and the expected emotional responses elicited by each product using the check‐all‐that‐apply (CATA) method. The 35 emotional terms adopted from the EsSense Profile® (King & Meiselman, 2010) were translated into Thai by a group of English–Thai bilinguals and translated back to English by another group for meaning validation (Hanmontree et al ., 2022). In this part, participants did not receive additional product information.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is essential to assess the emotional profiles of insect‐containing foods during new product development and marketing (Gutjar et al ., 2015; Leesuksawat et al ., 2019; Prinyawiwatkul, 2020; Gurdian et al ., 2021a, 2021b). In addition, previous researchers (Yang et al ., 2020; Hanmontree et al ., 2022) suggested that understanding and measuring emotional responses to the experience of eating certain products and to information about sustainability will also be important steps in product development. To date, few studies have focused on understanding the food‐evoked emotional profiles influenced by both insect consumption experiences and given product information.…”
Section: Introductionmentioning
confidence: 99%
“…Köster (2015) and Jiang (2014) reported that emotions affect consumers' eating behavior. Hanmontree (2022) presented several methods to measure traditional drinks' emotional and wellness profiles. Although the Kansei word enjoy had the lowest mean among all factors in component 2, it acquired the highest loading factor, indicating a factor influencing people to consume spice drinks.…”
Section: Component 2: Product Benefitsmentioning
confidence: 99%
“…Different questionnaire designs can influence the results of emotion and wellness assessments. Hanmontree et al assessed emotion and wellness profiles of herbal drinks using six different questionnaire designs [a questionnaire item written in the form of words vs. full sentences and three types of measuring methods: a rating scale, CATA, and RATA] [2]. They reported that using a full sentence did not provide a clear benefit over using some keywords, especially when using familiar words clearly understood by consumers.…”
Section: Introductionmentioning
confidence: 99%